Ukrainian Maritime Policy: Stranded in a Transit - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Kivalov, Sergiy (Helvetica Publishing Group, 2021)
Some aspects of the formation and realization of the modern maritime policy of Ukraine have been defined in the article. Its legal basis has been considered, its changes and updates have been monitored. The possibility and the ability to develop the documents of long-term planning in the maritime industry have been noted. At the same time, the belatedness and the lack of actual mechanisms for ensuring the execution of their norms lead to a stagnation of systemic reforms and a comprehensive update of public administration of the sphere. The attention is focused on the importance of a systematic approach to the transformation of legislative and law enforcement practices in the sphere of maritime and port activities in Ukraine, ensuring stability and continuity in their administration. The positive and negative practices in the exercise of powers by some subjects of realization of the maritime and port policy of Ukraine have been described. The pernicious practice of distance and situational intervention of a state in solving problems of the maritime and port industries as a strategic component of its political, social, and economic stability has been emphasized. Author suggests that introduction of modern methodology, such as maritime spatial planning may have positive impact on the effectiveness of Ukrainian maritime policy. When considering the development of the coastal regions as one of the directions of the maritime policy of Ukraine, it has been noted the advantages of creating and functioning the free economic zones in them. The characteristic of the experience of creation and work, as well as the specifics of such forms of trade facilitation (the preferential legal and financially-economic regimes, the presence of a particular specialization of entrepreneurial and investment activities, etc.), shows the economic expediency of granting such status to the port cities and the coastal regions. It has been noted that the free economic zones today are an active means of state policy, capable equally of reanimating depressed territory and giving an additional impetus to the regional points of growth.

У статті окреслено деякі аспекти формування та реалізації сучасної морської політики України. Розглянуто її правовий базис, простежено його зміни та оновлення. Відзначено можливість та здатність до розвитку документів довгострокового планування у морській галузі. При цьому запізнілість та відсутність реальних механізмів забезпечення виконання їх норм призводить до стагнації системних реформ та комплексного оновлення публічного адміністрування галузі. Акцентується увага на важливості системного підходу до трансформації законодавчої та правозастосовної практики у сфері морської та портової діяльності в Україні, забезпечення стабільності та наступності в їх адмініструванні. Охарактеризовано позитивні та негативні практики виконання повноважень деякими суб’єктами реалізації морської та портової політики України. Підкреслено згубність практики дистанціювання та ситуативного втручання держави у вирішення проблем морської та портової галузі як стратегічного компонента її політичної, соціальної та економічної стабільності. Автор зазначає, що впровадження такої сучасної методології, як морське просторове планування, може позитивно вплинути на ефективність морської політики України. Під час розгляду розвитку прибережних регіонів як одного з напрямків морської політики України відзначено переваги створення та функціонування у них вільних економічних зон. Характеристика досвіду створення та функціонування, а також специфіки таких форм сприяння торгівлі (пільгові правовий та фінансово-економічний режими, наявність певної спеціалізації підприємницької та інвестиційної діяльності тощо) свідчить про економічну доцільність надання такого статусу портовим містам та приморським регіонам. Зазначається, що вільні економічні зони сьогодні – це активний засіб державної політики, здатний як реанімувати депресивну територію, так й надати додаткового імпульсу регіональним точкам зростання.
Kivalov S. Ukrainian Maritime Policy: Stranded in a Transit / S. Kivalov // Lex Portus. - Vol. 7– Iss. 6. – Helvetica Publishing Group, 2021. - Р. 7-36.
Keywords: maritime policy; maritime doctrine; public administration; maritime and economic sector; maritime activity; maritime spatial planning; long-term planning; free economic zones; coastal territories; Ukraine; морська політика; морська доктрина; публічне адміністрування; морський сектор; морська діяльність; морське просторове планування; довгострокове планування; вільні економічні зони; прибережні території; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science